Code Equivalences Between Network Codes With Link Errors and Index Codes With Side Information Errors - Jae-Won Kim (IEEE Access, 2019)
In this paper, new code equivalence relationships between a network code and an index code are studied. First, for a given index coding instance, equivalent network coding instances are derived, where an index code achieving the maximum acyclic induced subgraph bound is converted to the corresponding network code and vice versa. Then, the code equivalence results are generalized to erroneous cases for both a given network coding instance and a given index coding instance, that is, code equivalences between a network code with link errors and an index code with side information errors.